Rationally designed CuFe2O4-mesoporous Al2O3 composite towards stable performance of high temperature water-gas shift reaction - Subramanian, Vijayanand; Gnanakumar, Edwin S.; Jeong, Dae-Woon; Han, Won-Bi; Gopinath, Chinnakonda S.; Roh, Hyun-Seog (Chemical Communications, 2013)
High temperature water-gas shift reaction was demonstrated for the first time on a CuFe2O4-mesoporous alumina nanocomposite between 350 and 550 degrees C with 70-80% CO-conversion using simulated waste derived syngas under realistic conditions. Despite high Al-content, the catalyst exhibited stable activity, which was attributed to the nano-architectured robust porous nature of alumina integrated with surrounding CuFe2O4.

Effect of composition and pretreatment parameters on activity and stability of Cu-Al catalysts for water-gas shift reaction - Mane, Rasika B.; Jeong, Dae-Woon; Malawadkar, Atul V.; Roh, Hyun-Seog; Rode, Chandrashekhar V. (ChemCatChem, 2014)
We investigated various Cu species responsible for highly efficient Cu-Al oxide catalyst for the water-gas shift reaction (WGSR). The formation of various Cu species was achieved by systematically varying the Cu-Al composition in the coprecipitated mixed Cu-Al oxides. The Cu-Al composition of 70:30 (Cu-Al-7) was the best for WGSR using the reformate gas composition. In addition, the Cu-Al-7 catalyst reduced under 100% H-2, was relatively stable with time on stream of 100 h, at higher gas hourly space velocity of 36201 h(-1). The structural investigation of our coprecipitated catalysts with varying Cu-Al compositions revealed the formation of nonzero oxidation state copper and metallic Cu to be essential for the observed WGSR activity. In addition, the highest activity and stability of Cu-Al-7 catalysts reduced under 100% H-2 at lower temperature was attributed to particle-size stabilization and a lower extent of Cu aggregation by Cu2O and boehmite phases, respectively, along with the formation of various Cu species during the activation protocol for 12 h. Complete CO2 selectivity without methanation was observed for all the Cu-Al compositions irrespective of their pretreatment conditions.
Keywords: aluminum; Copper; fuel cells; Hydrogen; reduction

Hydrogen production by the water-gas shift reaction using CuNi/Fe2O3 catalyst - Jha, Ajay; Jeong, Dae-Woon; Shim, Jae-Oh; Jang, Won-Jun; Lee, Yeol-Lim; Rode, Chandrashekhar V.; Roh, Hyun-Seog (Catalysis Science & Technology, 2015)
Incorporation of both Cu and Ni together into the crystalline lattice of Fe2O3 results in a significant increase in the catalytic activity and also suppresses the methanation reaction in the high-temperature water-gas shift (HT-WGS) reaction. CuNi/Fe2O3 exhibited the highest CO conversion with negligible CH4 selectivity at the extremely high GHSV of 101 000 h(-1) (X-CO = 85% at 400 degrees C). The high activity of CuNi/Fe2O3 catalyst is mainly due to the increase in the lattice strain and the decrease in the binding energy of lattice oxygen. In addition, X-ray photoelectron spectroscopy (XPS) results provide direct evidence for the formation of surface CuNi alloy, which plays a critical role in suppressing the methanation reaction. The detailed characterization by powder X-ray diffraction (XRD), XPS, BET, and H-2 temperature-programmed reduction (TPR) techniques was used to understand the role of dopants on host iron oxides in the enhancement of catalytic activity for HT-WGS reaction.

Mesoporous NiCu-CeO2 oxide catalysts for high-temperature water-gas shift reaction - Jha, Ajay; Jeong, Dae-Woon; Jang, Won-Jun; Rode, Chandrashekhar V.; Roh, Hyun-Seog (RSC Advances, 2015)
Mesoporous NiCu-CeO2 oxide catalysts were synthesized by using the evaporation-induced self-assembly method applied to the high-temperature, water-gas shift reaction (HT-WGS) between 350 to 550 degrees C. Nickel and copper loadings on mesoporous ceria were tailored to achieve high activity and selectivity by suppressing methane formation in HT-WGS. Among the prepared catalysts, NiCu(1 : 4)-CeO2 exhibited the highest selectivity to CO2 and H-2 with 85% CO conversion at a very high GHSV of 83 665 h(-1). The higher activity of the catalysts was due to the mesoporous architecture, which provides more accessible active sites for the WGS reaction. Powder X-ray diffraction (XRD), small angle X-ray scattering (SAXS), N-2-adsorption/desorption isotherm, high-resolution transmission electron microscopy (HR-TEM), and H-2-temperature-programmed reduction (TPR) techniques were used to understand the role of mesoporosity and bimetallic composition of various NiCu-CeO2 oxides in enhancing catalytic activity for HT-WGS.

Chromium free high temperature water-gas shift catalyst for the production of hydrogen from waste derived synthesis gas - Jha, Ajay; Jeong, Dae-Woon; Lee, Yeol-Lim; Jang, Won-Jun; Shim, Jae-Oh; Jeon, Kyung-Won; Rode, Chandrashekhar V.; Roh, Hyun-Seog (Applied Catalysis A-General, 2016)
A comparative study between monometallic (Me-CeO2, Me =Zn, Cu, Fe and Co) and Ni-doped bimetallic (Me-Ni-CeO2) catalysts has been performed in the high temperature water-gas shift (HT-WGS) reaction using waste derived synthesis gas. Experimental results revealed that Me-Ni-CeO2 exhibited higher catalytic performance than simple Me-CeO2 catalysts. Within the Me-Ni-CeO2 series, Co-Ni-CeO2 exhibited excellent and stable catalytic performance (CO conversion > 90%) at a very high GHSV of 143,000 h(-1). The existence of high" concentration of Ce3+ ions and oxygen vacancies on the catalyst surface were responsible for the increased WGS activity of Co-Ni-CeO2. In addition, Co-Ni-CeO2 maintains a stable performance for 50 h. However, commercial Fe2O3-Cr2O3 catalyst showed a steep decline from their initial CO conversion values 15-10% within 5 h. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: CeO2; Co-Ni-CeO2; Lattice strain; oxygen vacancies; Water-gas shift